Novel Approaches in the Management of Type 2 Diabetes and Associated Vascular Complications - Hari Kumar, K. V. S. (Annals of the National Academy of Medical Sciences (India), 2021)
Diabetes mellitus (DM) is growing in pandemic proportion and affects the affluent and developing nations equally. India has the dubious distinction of being known as the diabetes capital of the world. Epidemiological studies have shown that DM is under diagnosed and inadequately treated in our country. Insulin resistance and β-cell dysfunction are the two key pathophysiological determinants of the DM. The disease has metamorphosed during the last couple of decades with a significant change in the clinical presentation. Simultaneously, the therapeutic options for the management of DM have also increased in the last decade. This article highlights the research conducted by us over the last decade in the areas of pathogenesis, management, and complications of DM.
Keywords: gestational diabetes; insulin resistance; etiopathogenesis